2013
DOI: 10.1093/petrology/egt017
|View full text |Cite
|
Sign up to set email alerts
|

The Demir Kapija Ophiolite, Macedonia (FYROM): a Snapshot of Subduction Initiation within a Back-arc

Abstract: Since the late 1970s, it has been increasingly recognized that the petrology and geochemistry of ophiolites predominantly resemble those of lithological units from intra-oceanic subduction zones, ranging from nascentand fore-to intra-or back-arcs, ruling out analogy with modern oceanic ridge lithosphere. This conclusion is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 92 publications
1
47
0
1
Order By: Relevance
“…In the following subsections the available data on geological and geochemical characteristics of the East Vardar ophiolites in Romania [10,[29][30][31], Serbia [32][33][34][35][36], Macedonia [33][34][35][36][37] and Greece [33,[38][39][40], are summarized. The locations of the ophiolite massifs/outcrops addressed in this study are shown in Figure 1.…”
Section: East Vardar Ophiolitesmentioning
confidence: 99%
See 3 more Smart Citations
“…In the following subsections the available data on geological and geochemical characteristics of the East Vardar ophiolites in Romania [10,[29][30][31], Serbia [32][33][34][35][36], Macedonia [33][34][35][36][37] and Greece [33,[38][39][40], are summarized. The locations of the ophiolite massifs/outcrops addressed in this study are shown in Figure 1.…”
Section: East Vardar Ophiolitesmentioning
confidence: 99%
“…In the west, it is in contact with the metamorphic rocks of the Paikon unit that consists of Triassic marbles, clastic sediments, micaschists and various Upper Jurassic volcanic rocks that range in composition from rhyolite to basalt [47][48][49]. The northern part of the Guevgeli complex is the Demir Kapija ophiolites [33,34,37]. It is situated in southernmost Macedonia as an NNW-SSE elongated, 50 km long and 25 m wide and partially dismembered belt.…”
Section: Geologymentioning
confidence: 99%
See 2 more Smart Citations
“…U okviru IVZ (Peonias zone), ofioliti Demir Kapije kartirani su dvojako, kao da su navučeni preko SMM [6], [7] ili kao da je preko njih tektonski smeštena SMM [8]. Postoje sugestije da je ovaj ofiolitski kompleks formiran otvaranjem izalučnog basena iza Paikon luka [9], [10], i da je kasnije navučen zapadno na njega [11]. Sa druge strane, Robertson et al u [12] tvrde da su ovi ofioliti originalno navučeni preko SMM i kasnije, tokom kasne jure, ponovo navučeni prema zapadu.…”
Section: Uvodunclassified